Transcaval biopsy of a mediastinal mass compressing the superior vena cava. Issue 2 (20th December 2016) - Logaraj, Anthony; Edwards, Philip
Abstract : Imaging‐guided percutaneous chest biopsy is a commonly performed procedure and considered the minimally invasive gold standard for histopathological investigation of thoracic masses. Recognized complications include pneumothorax, air embolism, and seeding of the biopsy tract. We describe a novel approach to diagnostic sampling of a mediastinal mass in a critically unwell patient using a transjugular hepatic biopsy needle. Transcaval mediastinal biopsy may represent a safer alternative to percutaneous biopsy of mediastinal masses in critically unwell patients. Abstract : We describe a novel approach to diagnostic sampling of a mediastinal mass in a critically unwell patient using a transjugular hepatic biopsy needle. Transcaval mediastinal biopsy may represent a safer alternative to percutaneous biopsy of mediastinal masses in critically unwell patients.